Recurrent branch retinal arterial occlusions associated with plasminogen activator inhibitor-1 mutation - P. Storey, Philip; A. Philander, Shannon; J. Wong, Brandon; Rao, Narsing; C. Rodger, Damien (Journal of Ophthalmic Science, 2017)
A 57-year-old Hispanic female presented with 3 days of blurry vision in the left eye. Eight years prior, she had a branch retinal artery occlusion in the right eye and a hematologic work-up revealed a 4G/4G polymorphism in plasminogen activator inhibitor-1. With the current episode, she was found to have bilateral branch retinal artery occlusions and mild vitritis in the left eye, simulating a toxoplasma infection. An infectious and inflammatory work up, however, was negative and the vitritis resolved after a short course of steroids. Plasminogen activator inhibitor-1 mutations may be associated with an increased risk of retinal vascular occlusions.
Keywords: Retinal Artery Occlusion; Plasminogen Activator Inhibitor; Vitritis; Polymorphism; Mutation